The rhetoric of science and why it matters - Michael Ruse (Mètode Science Studies Journal: Annual Review)
When I started out as a philosopher of science, rather more than fifty years ago, the rhetoric of science did not exist. At least, it did not exist in philosophical circles. If you read the works of leading figures in the field like Karl Popper and Ernest Nagel, no attention was paid at all methods of convincing hearers – to language or argumentative gambits as such. It was all a matter of what the language said and the arguments proved. Indeed, there was a fair about of presupposition that science would be better off if it could be reduced to pure mathematics, without need of language at all and all arguments were straightforward deductions like you find in Euclidean geometry!